2020
DOI: 10.1111/jpc.14991
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in urban Aboriginal children: A cross‐sectional study of socio‐demographic patterns and associations with pre‐natal and current carer smoking

Abstract: Aim To describe socio‐demographic patterns of asthma prevalence in urban Aboriginal children and quantify associations between asthma prevalence and pre‐natal maternal and current carer smoking. Methods Analyses used carer‐reported survey data for 1290 urban Aboriginal children aged 2–17 years from the Study of Environment on Aboriginal Resilience and Child Health. Multilevel log‐binomial regression was used to estimate asthma prevalence ratios (PRs) for child‐ and family‐level socio‐demographic factors, pre‐n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Asthma prevalence is higher among Indigenous communities in Australia [ 38 ], and previous research has reported that asthma is a significant cause of morbidity and the most prevalent chronic respiratory condition among Indigenous populations, supporting this finding [ 39 , 40 ]. Various factors can contribute to the high asthma prevalence, including smoking, limited access to culturally appropriate health services, and social-environmental factors [ 40 , 41 ]. For example, low income can lead to poor living conditions and exposure to environmental asthma triggers such as household moulding or air pollution, as well as limited access to healthcare resources and medications, resulting in poor asthma control and a high prevalence.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Asthma prevalence is higher among Indigenous communities in Australia [ 38 ], and previous research has reported that asthma is a significant cause of morbidity and the most prevalent chronic respiratory condition among Indigenous populations, supporting this finding [ 39 , 40 ]. Various factors can contribute to the high asthma prevalence, including smoking, limited access to culturally appropriate health services, and social-environmental factors [ 40 , 41 ]. For example, low income can lead to poor living conditions and exposure to environmental asthma triggers such as household moulding or air pollution, as well as limited access to healthcare resources and medications, resulting in poor asthma control and a high prevalence.…”
Section: Discussionmentioning
confidence: 59%
“…This study found that areas with a high proportion of Indigenous people had a higher childhood asthma prevalence. Asthma prevalence is higher among Indigenous communities in Australia [38], and previous research has reported that asthma is a significant cause of morbidity and the most prevalent chronic respiratory condition among Indigenous populations, supporting this finding [39,40]. Various factors can contribute to the high asthma prevalence, including smoking, limited access to culturally appropriate health services, and socialenvironmental factors [40,41].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, it may also be the case that the reindeer-herding-related questions failed to separate out the small group of active reindeer herders, who are more exposed to risk factors such as cold climate exposure. Other risk factors, found for example in Canadian aboriginals, like smoking, urban residence, low education and low household income (7,19,20), were not relevant for this Sámi population.…”
Section: Discussionmentioning
confidence: 74%